Deskripsi Kebutuhan Guru Terhadap Pembuatan Bahan Ajar Berbasis Phenomenon-Based Learning Materi Fluida - Anggreani, Yulita; Sundari, Putri Dwi; Mufit, Fatni; Dewi, Wahyuni Satria (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Mataram, 2023)
Teaching materials are a crucial aspect in the process of learning. In the process of learning, it is necessary to have teaching materials that can increase students' understanding of concepts. One of the solutions that can be made is to bring students closer to everyday phenomena. This research was conducted as a basis for developing teaching materials based on phenomenon-based learning. The research type used is descriptive qualitative. The samples used were three physics teachers. The instruments for research used were interview sheets and literature review. The interview topics related to learning conditions at school, learning resources, learning models and obstacles faced in the process of learning. Based on the conditions in the field, teachers still really need learning resources that can increase the enthusiasm of students to learn, by bringing students closer to phenomena in the surrounding environment, so students can understand learning material quickly and correctly. The results shown that teachers need materials for teaching based on phenomenon-based learning to support student understanding, particulary in fluid material. Therefore, the research results can be used as a basis for research to develop teaching materials based on phenomenon-based learning